Social contract theory: a model for nation building in Nigeria / Yahaya I. Ibrahim and Sikiru Lanre Nurudeen - I. Ibrahim, Yahaya; Nurudeen, Sikiru Lanre (Universiti Teknologi MARA, 2022)
Social Contract Theory holds its origin to the three ancient philosophers, namely Thomas Hobbes (1588-1679 AD), John Locke (1632-1682 AD), and Jean –Jacque Rousseau (1712-1778 AD) who philosophized on state of nature and social contract. Although each of them had different notions of the concepts, they all agreed that it was the consent of the people to be organized into society for collective security. It also entails surrendering some or part of their personal liberties to a ‘’commonwealth’’. The commonwealth represents the modern day government. By implication, when individuals surrender their personal liberties to a commonwealth, the commonwealth is obligated to enforce laws that protect the individual. Perhaps it is in this context that social contract is regarded as one of the major explanations for the emergence of state system in the contemporary world. Nigeria is a nation-state with diverse elements wedged together by colonization and whose distaste for one another has not ceased in spite of efforts of successive governments. Unfortunately the founding of Nigeria was not based on a pact as suggested by the social contract theory. Again the colonial administrative system created some fundamental problems of integration which lingers on till date. This paper, using documentary research method examines the Nigerian state from colonial period and discovers that social contract theory is not appropriate to analyse the founding of the Nigerian state. It recommends that to build a nation out of Nigeria there is need to re-examine the process of integration of the different people that currently form it as well as its rule of engagement.